Body and organ weight data in 28-day toxicological studies in two mouse strains - Marxfeld, Heike Antje (Data Brief, 2019)
Toxicological studies were performed in an AAALAC (American Association for Laboratory Animal Care)-approved laboratory at BASF SE, Ludwigshafen, Germany, in accordance with the German Animal Welfare Act and the effective European Council Directive 2010/63/EU. Data were recorded in the BASF SE pathology data capture system. Historical control data (2008–2013) were compiled for a) Twelve 28-day studies performed according to OECD 407 with mice from Janvier C57BL/j Rj (J) and Charles River CD-1 (CRL), in total 73 control females and 73 control males, 5–8 weeks old at the beginning of the studies. Data collected: terminal body weight, organ weights of adrenal glands, brain, epididymides, heart, kidneys, liver, ovaries, prostate, seminal vesicles (with coagulating glands), spleen, testes, thymus, uterus. b) Eight immunotoxicity studies (duration of 28 days) performed according to EPA Health Effects Test Guidelines OPPTS 870.7800 with mice from Janvier C57BL/j Rj (J). 48 control females and 16 control males 5–7 weeks old at the beginning of the studies. Data collected: terminal body weight, mean absolute and relative weights of spleen and thymus. This data helps interpreting effects caused by treatment in toxicology studies in the mouse. Coefficients of variation were calculated and discussed in the accompanying research paper: “Variance of body and organ weights in 28-day studies in mice” (Marxfeld et al. 2019).